Influência de diferentes ingredientes nas propriedades tecnológicas de produtos sem glúten: uma revisão bibliográfica - Persi, Sophia Kriger Muzzy (Universidade Federal de São Carlos, 2025)
Wheat (Triticum spp.) holds a central position in the Brazilian baking industry, being widely used in the production of bread, pasta, and cookies, mainly due to gluten. The absence of gluten in formulations represents a major challenge because the technological properties provided by gluten proteins are lost, compromising the texture, volume, and appearance of the products. In this context, the food industry seeks alternatives capable of reproducing the functional properties of this compound through combinations of alternative flours and starches, substitute proteins, lipid ingredients, and hydrocolloids. The interactions among these ingredients are crucial for the success of the formulations, directly affecting physical properties—such as specific volume, color, and firmnessand sensory properties, including texture, taste, and consumer acceptance.The present study aimed to analyze the influence of different ingredients on the technological and sensory properties of gluten free products. A bibliographic research methodology was adopted, consisting of the selection, critical analysis, and systematization of information obtained from scientific articles in reliable databases such as SciELO, PubMed, and Google Scholar. The study identified the main technological challenges, the types of alternative ingredients used, and their effects on the technological and sensory properties of the products. The results of the review showed that the development of efficient formulations depends on an adequate understanding of the interactions among ingredients and the application of strategies and processing technologies that allow gluten-free products to achieve quality comparable to that of traditional products, thus meeting market demands.
Influence of different ingredients on the technological properties of gluten-free products: a literature review
Keywords: Inovações Tecnológicas; Ingredientes Alternativos; Indústria de Panificação; Technological Innovations; Alternative Ingredients; Baking Industry; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS; 3. Saúde e Bem-Estar; 9. Indústria, Inovação e Infraestrutura